Informatics Engineering and Information Science : International Conference, ICIEIS 2011 Kuala Lumpur, Malaysia, November 14-16, 2011 Proceedings, Part II - Abd Manaf, Azizah (Springer, 2011)
The ICIEIS 2011 conference explored new advances in digital information and data communications technologies. It brought together researchers from various areas of computer science, information sciences, and data communications to address both theoretical and applied aspects of digital communications and wireless technology. We hope that the discussions and exchange of ideas will contribute to advancements in the technology in the near future